Information and Communication Technology Usage in Record Keeping in Public Secondary Schools in Ilemela Municipality, Tanzania - Stella Masegenya; Prospery Mwila (International Journal of Information Systems and Informatics, 2023)
The use of Information and Communication Technology (ICT) in education supports, improves, and optimises the dissemination of knowledge. International studies have demonstrated that ICT can increase student learning and teaching techniques. This study assessed the usage of Information and Communication Technology in Record Keeping in public secondary schools in Ilemela Municipality, Tanzania. Specifically, the study sought to identify types and roles of ICT appliances in school record keeping in public secondary schools, and to describe the attitudes of members of school community towards the usage of ICT in school record keeping in public secondary schools. The study was guided by Diffusion of Innovation Theory and Adaptive Structuration Theory. It adopted a mixed research approach and a convergent parallel research design. The target population of the study was 1032 and sample size comprised 108 respondents, sampled through probability and non-probability techniques. Research instruments included questionnaires and interview guide. Descriptive statistics and thematic analysis were used to analyse quantitative data and qualitative data respectively. The synthesis of the findings indicated that there is inadequate application of ICT in record keeping in public secondary schools because of the inadequacy of ICT facilities, lack of ICT trained personnel and insufficient funds required for overall maintenance and management of ICT related software. Furthermore, it was revealed that members of the school community have positive attitudes towards the use of ICT in record keeping in public secondary schools. The study concluded that ICT usage in record keeping is vital, it plays potential role in record keeping. Therefore, the government through the ministry responsible for education should provide public secondary schools with sufficient and modern ICT facilities that support/enhances the current practices in school administration and management